Analisis Pengaruh Pendidikan, Pelatihan dan Disiplin Kerja terhadap Pengembangan Karir Melalui Kinerja Pegawai sebagai Variabel Intervening (Kajian Studi Literatur Manajemen Sumber Daya Manusia) - Katarina Umiti Peuuma, Maria; E.H.J. FoEh, John; A. Manafe, Henny (Dinasti Review Publisher, 2023)
The most important asset in an organization is human resources because human resources play a role as executors of company policies and operational activities and determine the success of an organization. Therefore, organizations are required to carry out career development for their human resources so that organizational goals can be achieved. This article discusses the review of the literature on the factors that influence human resource career development, namely education, training, work discipline and employee performance as intervening variables. The results of this study are education has a significant effect on career development; training has a significant effect on career development; work discipline has a significant effect on career development; education has a significant effect on employee performance; training has a significant effect on employee performance; 6) Work discipline has a significant effect on employee performance; employee performance has a significant influence on career development; education, training and work discipline have a significant and simultaneous effect on employee performance; and education, training and work discipline have a significant and simultaneous effect on career development.